Optimization of storage conditions for the detection of Heat Shock Protein 70 (HSP70) from salivary glands of field collected Aedes albopictus / Nur Azimah Sulong - Sulong, Nur Azimah (2015)
Aedes albopictus is a significant vector capable of transmitting dengue virus (DENV) and Chikungunya virus (CHIKV). Aedes albopictus has heat shock protein 70 (HSP70) protein molecules that are receptor complexes associated with virus replication. Thus, it have been implicated in viral entry, propagation, and transmission of DENV. This study was performed to determine the optimum media and laboratory conditions for the detection of HSP70 extracted from salivary gland tissues from field collected Aedes albopictus mosquitoes. Proteins were subjected to a variety of temperature and media, and its 70 kDa profile, analysed by sodium dodecylsulphate polyacrylamide gel electrophoresis (SDS-PAGE). Based on the protein profile analysis, protein band of 70 kDa was distinctly detected when preserved in phosphate buffered saline (PBS) and stored at 4°C for a period of 7 days. This protein is analogous to the protein synthesized by dengue infected Aedes albopictus. It is required for the entry of DENV in human cells such as in human monocytes and macrophages. Thus, further study utilising amino acid sequencing must be performed to confirm the presence of HSP70 which has been revealed by SDS-PAGE protein analysis.